THE SIGNIFICANCE OF SIGNAL TOWERS IN THE PAST - Kanaatov Esimkan Elsuyer ugli (Web of Journals Publishing, 2024)
The article tells about the historical monuments of the X-XIII centuries in the Aral Sea region - the role of lighthouse towers for the life of the population in the past. The author gives interesting information about the characteristics of lighthouses located in the southeast of Ustyurt and on the Sultan-Uvais ridge along the banks of the Amu Darya.
Keywords: South-Eastern Ustyurt, Aral Sea region, signal towers, lighthouse, caravan route, Mongols, nomads.